RESEARCH ON DESIGNING AND OPTIMIZATION OF MILLING TOOL:A REVIEW (MT) - WANG DongMing; MENG LongHui; ZHANG Hao; WANG Hua (Jixie qiangdu)
The research progress of designing and optimization of milling tool is summarized. The design process of cutting tools has greatly improved and optimized according to the existing problems in the field of cutting and manufacturing. The research progresses of the improvement and optimization of the milling tool in five aspects, such as: Machining quality, tool wear, machining vibration, chip removal performance and machining efficiency are mainly described and summarized. Finally, it analyzes the existing technical problems, and puts forward the corresponding prospects for the later research of NC milling tool technology.